Hypoxia-induced factor-1α and markers of inflammation in patients with ischemic stroke - L. P. Pivovarova; I. A. Voznyuk; I. V. Osipova; O. B. Ariskina; E. A. Gogoleva; M. V. Prokhorova; N. G. Karpova (Медицинская иммунология)
Ischemic stroke (IS) occurs as a result of local disturbance of hemocirculation and hypoxia in the brain tissue. Hypoxia-inducible factor-1α (HIF-1α), which is involved in the regulation of tissue oxygen levels, plays an important role in the pathophysiology of stroke, including neuronal survival, neuroinflammation, angiogenesis, glucose metabolism, blood-brain barrier permeability, and is important in IS outcomes. The purpose of the study was to determine the relationship between blood levels of HIF-1α and the degree of neurological deficit in the acute period of IS and the outcome of the disease. We examined 58 people with IS aged 73 (67-81) years. Patients were divided into two groups – discharged and dead. The severity of stroke (NIHSS), neurological deficit, comorbidity index, blood levels of HIF-1α, p53 protein, interleukin-6, cystatin C, CRP, creatinine, hematological parameters were determined at admission, on days 3 and 10 of the disease. At admission the blood levels of HIF-1α was lower than in the comparison group and remained reduced until the 10th day. On day 10 the association of HIF-1α with neurological deficit, comorbidity index and disease outcome was determined. We observed a feedback of HIF-1α with the content of erythrocytes, hemoglobin and hematocrit, which can be regarded as a reflection of the hemic component of mixed hypoxia. In dead patients, an increased blood level of cystatin C was detected, which was associated with HIF-1α concentrations. In all periods of observation of IS, a correlation between cystatin C and creatinine and CRP levels was noted. These results may indicate dysfunction of endotheliocytes, inflammation associated with hypoxia in IS. The prognostic significance of the blood level of HIF-1α on the 10th day for the outcome of IS was AUC = 0.900. Blood levels of HIF-1α in the acute period was associated with the severity of IS and the outcome of the disease.